La desintegración familiar en el aprendizaje de los estudiantes. - Millingalle Lovato, Nataly Soledad (2018)
Family disintegration is a social factor that affects many families every day, causing great consequences, especially among the most vulnerable in the home. Due to this reason, the research carried out in this project is developed with the objective of analyzing the factors of family disintegration and its influence on student learning, the studies conducted reveal the concern that the issue has in secondary schools which is important for the implications it has on the academic results of dozens of students who experience this type of conflict in their families. The methodological design of the research is part of the quantitative approach that starts from the study of numerical data analysis, through statistics supported by bibliographic / documentary and field research that allow the development of the present investigation through the application of the survey techniques and observation. The survey is designed for the group of children with the objective of knowing what are the family factors that do not allow their good development in learning. The importance of family disintegration in student learning lies in knowing more about the effects and factors that these affect the student's learning, the psychological, physical, behavioral expression and the role of the teacher in this problem. Many Ecuadorian families live a situation of disintegration, but those decisions adopted by adults about the future of their relationship end up affecting in different ways in its many facets that end up being ignored by the teacher and the parents themselves without realizing the great damage that are causing in children.